Structural properties and surface oxidation states of sputter‐deposited TiO2−x thin films. (15th February 2021) - Jana, Swapan; Debnath, Anil Krishna; Putta, Veerender; Bahadur, Jitendra; Chauhan, Anil Kumar; Bhattacharya, Debarati
Abstract : Titanium dioxide (TiO2− x ) films were deposited on silicon (100) substrates from pure titanium (Ti) targets using direct current magnetron sputtering technique. TiO2− x thin films were grown in the thickness range of 515–672 Å with varying sputter powers of 75 and 100 W, at both room temperature (RT) and 200°C substrate temperature ( T s ). Structural and compositional characterization of the films, which included surface morphology and study of surface chemical states, was performed. The influences of sputter power and substrate temperature on these parameters were specifically analyzed. Grazing incidence X‐ray diffraction showed that the thin films were amorphous at RT and crystallinity could be achieved only at T s . The latter showed anatase phase at sputter power of 75 W and transformed into anatase–rutile mixed phase at 100 W. The thickness, roughness, and mass density of the thin films were measured using X‐ray reflectivity. It was observed that for T s films, the roughness and mass density increased with higher sputter power. Field emission scanning electron microscopy and atomic force microscopy also corroborated this surface roughness result. It was observed from X‐ray photoelectron spectroscopy that the core levels of Ti‐2p3/2 and O‐1s and their corresponding binding energies indicated that only one of the Ti oxidation states, i.e., Ti 4+, existed in the films. This work provides insight about the growth of TiO2− x thin films influenced by T s deposition and different sputter power.